2022
DOI: 10.1155/2022/9506078
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Deficiency Tolerance and Responsiveness of Durum Wheat Genotypes in Ethiopia

Abstract: Development of low-nitrogen (N) tolerant and N-responsive durum wheat genotypes is required since nitrogen efficiency has emerged as a highly desirable trait from economic and environmental perspectives. Two hundred durum wheat genotypes were evaluated at three locations under optimum (ON) and low (LN) nitrogen conditions to screen genotypes for low-nitrogen tolerance and responsiveness to an optimum N supply. The results showed significant variations among the durum wheat genotypes for low-N tolerance and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The results indicated that tolerant high-yielding can be identified effectively using these tolerance indices. (Aga et al, 2022;Krishnamurthy et al, 2016;Singh et al, 2017;Singh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that tolerant high-yielding can be identified effectively using these tolerance indices. (Aga et al, 2022;Krishnamurthy et al, 2016;Singh et al, 2017;Singh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes thus selected exhibited desirable physiological and biochemical traits like relative water content, stomatal conductance, chlorophyll content and proline content. The stress indices have also been employed in diverse crop and stress conditions (Aga et al, 2022; Krishnamurthy et al, 2016; Singh et al, 2017; Singh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%